People of Destiny : Louis Armstrong - Richards, Kenneth G., 1926- (Chicago, Childrens Press, 1967)
1. Armstrong, Louis
Includes Bibliography & index
Basic Ed. Students
Keywords: Armstrong, Louis, -- 1901-1971.